Pengaruh Kecerdasan Emosional, Perilaku Kewargaan Organisasional Terhadap Kinerja Pegawai dengan Kualitas Kehidupan Kerja sebagai Variabel Mediasi pada Sekolah Tinggi Ilmu Ekonomi Sabang Banda Aceh - Khairunnisa, Anis; Iskandar, Raihan; Luthfi, Luthfi (Aceh Cooperative Care, 2024)
This research was conducted at STIES Banda Aceh, with research objects being 31 lecturers and 13 educational staff. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (SEM-PLS) method with the SmartPls 4.0 program. The research results show that emotional intelligence and organizational citizenship behavior have a positive and significant influence on employee performance. Other results show that the influence of Emotional Intelligence, Organizational Citizenship Behavior on Performance and fully mediated by Quality of Work Life has a positive and significant influence. The higher the Emotional Intelligence and Organizational Citizenship Behavior, the higher the Quality of Work Life which will ultimately improve employee performance.